Metal Nanoparticle: Synthesis, Properties, and Their Dermatological and Cosmetic Impacts - Patil Kishori Sandip (Recent Trends in Cosmetics, 2025)
Nanoparticles (NPs) are materials with dimensions under 100 nm and various shapes, such as spheres and rods. Their advancement offers transformative potential in medical and healthcare fields. The increased application of NPs across molecular biology, chemistry, medicine, and material science reflects their growing importance. Due to their large surface area, NPs enhance substance delivery through the skin, benefiting cosmetic applications by improving penetration, efficacy, and targeted delivery of active ingredients.With the prominent uses in dermatology as antioxidants and anti-reflectants, metal nanoparticles (NPs) have recently attracted the attention due to their unique physical and chemical characteristics when compared to their bulk counterparts. Metal NPs, particularly silver and gold, exhibit significant antibacterial properties and have diverse synthesis methods, including chemical, physical, and the biological approaches. Biological synthesis using organisms like fungi and plants offers an environmentally friendly alternative, reducing toxic byproducts and energy consumption while enhancing biocompatibility and scalability for potential applications in medical, pharmaceutical, and cosmetic industries.Nanoparticles’ high surface area-to-volume ratio facilitates efficient interaction with other substances, making them valuable in treatments that minimize harm to healthy cells. This review explores the types, synthesis, and applications of metal-based NPs, highlighting their antibacterial activity and potential for enhancing skincare and other industries.
Keywords: Dermatology; antimicrobial activity; cosmetics; green synthesis; metal nanoparticles; silver and gold nanoparticles; skin penetration